2009
DOI: 10.1002/jsfa.3539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine colostrum on the growth inhibition and differentiation of human leukemic U937 cells

Abstract: BACKGROUND: Colostrum is the breast milk of female mammals produced within in a short time after giving birth. It is thought to protect neonates from infection as well as to facilitate immune system maturation. In this study the effect of bovine colostrum on the proliferation and differentiation of human leukemic U937 cells was investigated to understand more about its immunomodulatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Growth inhibition of the U937 cells treated with PIS‐, ALS‐ and FLS‐MNC‐CM (500 µg/mL) for 3 days was 59.36, 55.00 and 57.48%, respectively (data not shown). The results were similar to those reported by Ma et al . (2009) who found that the inhibition of U937 growth using MNC‐CM prepared with colostrums collected on the second postpartum day at 100–800 µg/mL was 43.3 to 55.9%.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Growth inhibition of the U937 cells treated with PIS‐, ALS‐ and FLS‐MNC‐CM (500 µg/mL) for 3 days was 59.36, 55.00 and 57.48%, respectively (data not shown). The results were similar to those reported by Ma et al . (2009) who found that the inhibition of U937 growth using MNC‐CM prepared with colostrums collected on the second postpartum day at 100–800 µg/mL was 43.3 to 55.9%.…”
Section: Resultssupporting
confidence: 93%
“…2005); cells prepared with the water extract of rice ( Oryza sativa L.) at 500 µg/mL was 35% (Liao et al . 2006); bovine skimmed colostrums collected on the second day postpartum at 800 µg/mL was 50% (Ma et al . 2009); and semi‐purified polysaccharides of Antrodia camphorate at 100 µg/mL was 55% (Liu et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations